The Effect of Functional Alienation in Organizational Stability Analytical study in the Ready - Wear Factory in Najaf (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The aim of this research is to determine the effect of functional expatriation on its indicators (disability, illiteracy, and immorality) on organizational stability with its indicators (commitment, satisfaction, loyalty), in addition to determining whether there are significant differences in the responses of workers in the ready-made garment factory in Najaf.The research community consisted of individuals working in the garment factory in Najaf (142) workers. The research sample was selected by random stratified method (75). The research was based on analytical descriptive method. The second part was based on a questionnaire developed and developed to measure the objectives of the research and hypothesis testing. It consisted of two parts representing the first part in the functional expatriation with its indicators, while the second part contains organizational stability with its indicators. SPSS was used in the analysis of data using the statistical package program For social science. The researcher concluded that the workers in the ready-made garment factory in Najaf suffer from a sense of expatriation, and that the most common manifestations of expatriation are the deficit followed by the non-exclusivity And then inconsequential. The researcher also presented a number of suggestions on the management of the plant, the most important of which was: attention to the design and internal arrangement of the building of the research plant in accordance with the nature of the products produced, which reduces the phenomenon of expatriation of employees